HUBUNGAN PEMANFAATAN SUMBER BELAJAR GEOGRAFI PERPUSTAKAAN SEKOLAH DAN MINAT BACA DENGAN HASIL BELAJAR SISWA KELAS XI IPS MAN ACEH SINGKIL - Musfina, Ririn; Desfandi, Mirza; Jummi, Cut Vita Rajiatul (Universitas Syiah Kuala, 2025)
Utilization of learning resources is one source for increasing learning productivity. Reading interest is a person's interest or tendency to read without compulsion. The research aims to determine whether there is a positive and significant relationship between the use of geography learning resources in the school library and interest in reading and the learning outcomes of class XI IPS students at MAN Aceh Singkil. This research uses a quantitative approach and correlation research type. The population in this study were all students of class XI IPS MAN Aceh Singkil, totaling 28 students taken using saturated sampling techniques. Research data was collected using documentation and questionnaires. The results of the research show a relationship between the use of geography learning resources in the school library and interest in reading with the learning outcomes of class XI IPS students in the Strong category. The results of the multiple correlation analysis were 0.66, which means there is a strong relationship, the coefficient of determination is 43%. The significance test results show 10.5. This means that there is a significant relationship between the use of geography learning resources and interest in reading and the learning outcomes of class XI IPS students at MAN Aceh Singkil.